2018
DOI: 10.1080/1478422x.2017.1372246
|View full text |Cite
|
Sign up to set email alerts
|

Double-loop electrochemical potentiokinetic reactivation behaviour of continuously cooled SUS329J4L duplex stainless steel

Abstract: Sigma phase generally precipitates in duplex stainless steel during slow cooling, which usually causes loss in both corrosion resistance and fracture toughness. To develop a non-destructive method to detect the sigma phase in duplex stainless steel for in situ use in the quality management of large structures, the double-loop electrochemical potentiokinetic reactivation behaviour of continuously cooled duplex stainless steel SUS329J4L at different cooling rates was investigated under different conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In previous XRD analysis 16) , the amount of σ phase in samples with the same composition as used in this study that had been continuously cooled with τ = 3115 s (0.2 K/s vs. 1073 ~ 773 K) and 5500 s (0.1 K/s) was 5.9% and 13.4% respectively, but no σ phase was detected when τ was 1795 s (0.3 K/s) or smaller. On the other hand, the Charpy absorbed energy of the sub-size samples at room temperature continually decreased with the time constant from τ = 445 s (1.0 K/s) to 28000 s (0.02 K/s).…”
Section: Epr Polarization Curves Of Laboratory Samplesmentioning
confidence: 67%
See 2 more Smart Citations
“…In previous XRD analysis 16) , the amount of σ phase in samples with the same composition as used in this study that had been continuously cooled with τ = 3115 s (0.2 K/s vs. 1073 ~ 773 K) and 5500 s (0.1 K/s) was 5.9% and 13.4% respectively, but no σ phase was detected when τ was 1795 s (0.3 K/s) or smaller. On the other hand, the Charpy absorbed energy of the sub-size samples at room temperature continually decreased with the time constant from τ = 445 s (1.0 K/s) to 28000 s (0.02 K/s).…”
Section: Epr Polarization Curves Of Laboratory Samplesmentioning
confidence: 67%
“…The σ phase precipitates in duplex stainless steel during both isothermal aging between 973 ~ 1173 K 5)-8),11)- 14) and continuous cooling from 1338 K 15)- 17) . In our previous study, XRD analysis showed that the amount of σ phase in SUS329J4L steel cooled at 0.02 K/s from 1073 to 773 K was 22.9% 16) . During isothermal aging, carbides (M23C6) form at the γ/α boundary and then grow into the neighboring γ phase 11) .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…7 shows the observed thickness of passive film formed in water on the sigma (σ) and gamma prime (γ′) phases in sensitized SUS439J4L duplex SS after continuously cooling at 0.02 K/s between 1073 and 773 K. The solution-treated SUS329J4L generally contains two phases, ferrite (α) and austenite (γ), before sensitization. During the continuous slow cooling, the α phase changes to fine σ phase with high Cr content and γ′ phase with low Cr content to induce prior corrosion around σ phase 43 . In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was to serve as a thickness reference, as it is inert under all conditions to which it was exposed in this study. SUS329J4L duplex SS of chemical composition Fe-0.029C-0.43Si-0.73Mn-0.038P-0.005S-24.19Cr-5.68Ni-2.68Mo-0.14 N, and annealed by continuously cooling at 0.02 K/s between 1073 and 773 K, with ferrite (α), austenite (γ, γ′) and sigma (σ) phases 43 , was used after being polished and cleaned as above.…”
Section: Methodsmentioning
confidence: 99%